Vitamin D for inflammation biomarkers in coronary artery disease: A protocol for systematic review and meta-analysis. Issue 31 (31st July 2020) - Wang, Yiru; Zhang, Yifan; Wei, Jing; Du, Wenting; Ding, Jie; Zhang, Yiyi; Zhang, Na; Mao, Meijiao; Liu, Ping
Abstract: Background: Coronary artery disease (CAD) is a clinically common coronary heart disease. Vitamin D might be beneficial in CAD patients through its favorable effects on inflammation biomarkers. This study will be performed to examine the effects of Vitamin D supplementation on inflammatory markers in CAD patients. Methods: We will search the electronical databases and hand-searching journals or reference lists. The study screening and data extraction will be carried out by 2 investigators independently. The primary outcome is inflammatory biomarkers of peripheral blood. Secondary outcomes are triglyceride, total cholesterol, high-density lipoprotein cholesterol levels, low-density lipoprotein cholesterol, and blood pressure. Review Manager (RevMan, version 5.3; The Nordic Cochrane Centre, Copenhagen, Denmark: http://community.cochrane.org ) V.5.3 software will be used to compute the data. Results: The results of the study will provide a reliable evidence to assess the efficacy of Vitamin D supplement on inflammation biomarkers of CAD patients. Conclusion: The conclusion of our systematic review will answer whether Vitamin D is an effective intervention to relieve inflammation of CAD patients. Ethics: Because all of the data used in this review has been published, this review does not require ethical approval. Registration number: INPLASY202060072.